Assessment of glucose levels in cyst fluid aspirates to evaluate cellular metabolism - Shailja Chatterjee; Asha Karadwal (Wolters Kluwer Medknow Publications, 2017)
Aim and Objectives: The aim of the study was to analyze glucose content of cyst fluid to assess the cellular metabolism. Objectives were to analyze glucose level in cyst aspirates of dentigerous, odontogenic keratocysts, radicular, and residual cysts to analyze pathophysiological differences. Materials and Methods: Cyst fluid aspirates obtained from radicular cysts (n = 5), dentigerous cysts (n = 6), odontogenic keratocysts (n = 2), and residual cyst (n = 1) were assessed for glucose levels using Trinder's method. Statistical analysis was done by calculating mean ± standard deviation (SD) values for glucose levels. Analysis of variance test was employed to obtain P value. Results: No significant correlation was obtained among the various cysts studied. Mean ± SD values suggested highest metabolic glucose metabolism in radicular and odontogenic keratocysts. Dentigerous cyst showed intermediate values while residual cysts had least glucose content due to its quiescent nature. Conclusion: Cellular activity is similar in all the studied cysts but their expansile properties can be attributed to multiple other factors such as albumin, immunoglobulins, and keratin